INBORN IMMUNITY: MECHANISMS OF REALIZATION AND PATHOLOGICAL SYNDROMES - P.F. Litvitsky; T.G. Sinel'nikova ("Paediatrician" Publishers LLC, 2009)
This lecture (the first one of planned) describes the structure and function of inborn immunity factors, as a component of system of immunobiological surveillance of organism; also this work gives information of mechanisms of detection of foreign antigens with special classes of phagocytic receptors (appearance-recognizing, toll-like, NOD, mannose, lektine, scavenger, receptors of complement system factors, etc.). Authors describe syndromes of insufficiency of immunobiological surveillance system, developing as a consequence of disorders of reception of foreign agents with phagocytes. Key words: inborn immunity, adaptive immunity, appearance-recognizing receptors, pathogen-associated molecules, immunopathological syndromes. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):52-58)